Amniotic fluid embolis the pathophysiology, diagnostic clue, and blood biomarkers indicator for disease prediction - R. Suvannasarn; T. Tongsong; P. Jatavan (Clinical and Experimental Obstetrics & Gynecology)
Objective: This article aims to review and provide more understanding of current knowledge of amniotic fluid embolism regarding pathophysiology, diagnostic criteria, risk factors, indicating biomarkers, treatment strategies and outcomes of some case reports. Study design: A systematic literature review was performed using the PubMed database, restricted to articles published in English from 1992 to 2018. Original research, case reports, guideline recommendations, and review articles were reviewed in this study. Summary: Amniotic fluid embolism (AFE) is a rare catastrophic obstetric condition defined by clinical manifestations of pregnancy with sudden onset of cardiopulmonary arrest, consumptive coagulopathy or neurological deficits without other explainable illnesses. The incidence varies from 1.7-14.8 cases per 100,000 worldwide. The current understanding of AFE pathophysiology includes fetal components obstructing maternal microvessels with subsequent anaphylactoid reaction. Maternal pulmonary vasospasm and hematologic activation occur later, followed by heart failure and sudden cardiovascular collapse. Some of the possible risk factors for AFE include; 1) Maternal risk: age over 35 years, hypertensive disorder and diabetes mellitus; 2) Fetal risk: polyhydramnios, multiparity, non-vertex at delivery, fetal distress and fetal macrosomia; 3) Obstetric risks: amniocentesis, artificial amniotic fluid injection, oxytocin infusion, and placental abruption. Some of the useful biomarkers have been proposed including zinc coproporphyrin-1, squamous cell carcinoma antigen, carcinoembryonic antigen, cancer antigen 125, Siatyl Tn, monoclonal antibody TKH-2, C3, C4, tryptase, insulin-like growth factor binding protein-1, C1 esterase inhibitor. Management of AFE requires immediate basic life support and advanced cardiac life support. Adequate oxygenation, ventilation, coagulopathy correction, and appropriate vasopressors are recommended. However, the outcome prediction of AFE remains challenging.